A Critique on the Book Hermeneutics and Religious Modernity - Ali Abedi Renani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the 1990s, the Iranian intellectual community faced a trend of religious modernization. This new spirit flowed in the academic and seminary community, and the market for scientific debate and critique flourished. From this point of view, the age of righteousness has replaced the age of duty, and as a result, they demanded a new interpretation of religious texts and task-oriented jurisprudence. The common denominator of this movement is that pure understanding is not possible, and any understanding is preceded by pre-understandings. For this reason, this movement has been inspired by hermeneutic theories that seek to understand the nature and mechanism of understanding. The book under review examines the influence of Heidegger and Gadamer's philosophical hermeneutics on the religious modernization movement. In this article, I describe, analyze and evaluate the main claims of the book. It seems that Gadamer's philosophical hermeneutics is not a good model for analyzing the current of religious modernism, and although they have similarities, it is in some ways in conflict with the foundations of this movement.